The effect of indium doping on structural, electrical conductivity, photoconductivity and density of states properties of ZnO films - Benouis, C. E.; Benhaliliba, M.; Sanchez Juarez, A.; Aida, M. S.; Chami, F.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2010)
The effect of indium doping on structural, electrical conductivity, photoconductivity and density of states properties of IZO thin films has been investigated. X-rays diffraction spectra show that the IZO films are polycrystalline of wurtzite structure with preferential orientation of (002) direction. The IZO thin film for doping level of 2% exhibits the lowest resistivity of 6 x 10(-3) (Omega cm) compared to undoped ZnO of 17 (Omega cm). The optical gaps of the IZO thin films were determined using optical transmission spectra and the obtained optical band gap value increases slightly from 3.28 eV to 3.35 eV due to the indium doping. The IZO film indicates a strong photoconductivity with indium doping level. The density of states, traps concentration and relaxation time for the films were calculated using Laplace transform method and these parameters change with In doping level. It is evaluated that In doping has an important effect on the electronic and optical properties of ZnO thin films. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: ZnO; Spray pyrolysis; Indium doping; Photoconductivity